Zimbabwe : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper reports economic developments in Zimbabwe during the 1990s. In 1991, the government officially launched its comprehensive Economic and Structural Adjustment Program-covering fiscal years 1991 through 1995-to strengthen growth and employment prospect. Despite the success achieved in carrying out a number of structural reforms, persistently large budget deficits presented a serious impediment to growth. The failure to bring the government budget under control was reflected in high levels of spending, which contributed to an uncompetitive exchange rate and necessitated excessive borrowing and high real interest rates.